Efek Kuning Telur Terhadap Motilitas Sperma Ikan Lukas (Puntius bramoides Val) Pascakriopreservasi - Pertiwi, Primasari; Abinawanto; Farisi, Salman (CV. Multi Kreasi Media, 2024)
The research aims to determine the effect of several concentrations of egg yolk as an effective natural cryoprotectant for cryopreservation and to analyze the quality of lukas fish spermatozoa (Puntius bramoides Val) 48 hours after cryopreservation. This research used a 9 treatments and 4 replications. The concentration of egg yolk used as a cryoprotectant was 0% (negative control), 5%, 7%, 9%, 11%, 13%, 15%, 17%, and 1% Carboxymethyl Cellulose (CMC) was used as a positive control. The results showed that the use of several concentrations of egg yolk as a natural extracellular cryoprotectant was able to significantly influence (P<0.005) the quality of Lukas fish spermatozoa 48 hours after cryopreservation. The use of egg yolk concentration of 9% is the optimum concentration in maintaining the motility of Lukas fish spermatozoa with the average percentage obtained each being 80.45 ± 0.93%.